Calabi-Yau Varieties and Mirror Symmetry 2003
DOI: 10.1090/fic/038/06
|View full text |Cite
|
Sign up to set email alerts
|

Calabi-Yau manifolds over finite fields, II

Abstract: We study ζ-functions for a one parameter family of quintic threefolds defined over finite fields and for their mirror manifolds and comment on their structure. The ζ-function for the quintic family involves factors that correspond to a certain pair of genus 4 Riemann curves. The appearance of these factors is intriguing since we have been unable to 'see' these curves in the geometry of the quintic. Having these ζ-functions to hand we are led to comment on their form in the light of mirror symmetry. That some r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
198
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(207 citation statements)
references
References 21 publications
7
198
1
1
Order By: Relevance
“…In [CdOV1] it was shown that the number of rational points of the quintic Calabi-Yau manifolds over F p can be given in terms of the periods; our calculations verify this relation for the octic. The periods satisfy a system of differential equations known as the Picard-Fuchs equations, with respect to the parameters.…”
Section: The Arithmetic Of Calabi-yau Manifoldssupporting
confidence: 72%
See 2 more Smart Citations
“…In [CdOV1] it was shown that the number of rational points of the quintic Calabi-Yau manifolds over F p can be given in terms of the periods; our calculations verify this relation for the octic. The periods satisfy a system of differential equations known as the Picard-Fuchs equations, with respect to the parameters.…”
Section: The Arithmetic Of Calabi-yau Manifoldssupporting
confidence: 72%
“…In order to study these questions, we shall be considering families with up to two parameters, and use methods very similar to [CdOV1,CdOV2]. In particular, we study a one parameter family of K3 surfaces and a two parameter family of CalabiYau threefolds, octic hypersurfaces in weighted projective space P 4 (1,1,2,2,2) [8], the mirror symmetry of which was studied in detail in [CdOFKM].…”
Section: The Arithmetic Of Calabi-yau Manifoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore of interest to consider the behavior of families of varieties and analyze their arithmetic structure as their moduli change. This line of thought has already been followed in recent work [34,35,36]. These interesting papers address, among other issues, the question of what happens to the reduced variety at the conifold locus.…”
Section: Modularity Of a Phase Transitionmentioning
confidence: 87%
“…For instance, Candelas et al [6] have studied the zeta functions of some Calabi-Yau threefolds occurring as toric complete intersections, motivated by considerations of mirror symmetry.…”
Section: Toric Complete Intersectionsmentioning
confidence: 99%